The impact of preliminary patient hydration on physiological [18F]PSMA-1007 uptake in the urinary bladder on PET/CT - T. L. Antonevskaya; A. I. Khalimon; O. V. Mukhortova; M. M. Khodzhibekova; A. I. Nikiforuk; D. D. Zubkov; G. F. Khamadeeva; D. Yu. Khodakova; T. N. Lazutina; I. V. Pylova; A. V. Leontyev; I. P. Aslanidi (Исследования и практика в медицине)
Оne of the most commonly used fluorine‑18 labeled prostate-specific membrane antigen (PSMA) ligands in positron emission tomography combined with computed tomography (PET/CT) is [18F]PSMA‑1007. In comparison to other clinically available PSMA radioligands characterized by renal clearance, [18F]PSMA‑1007 exhibits predominantly hepatobiliary excretion. It allows a better assessment of the pelvic area in patients with prostate cancer (PCa). Nevertheless, in our clinical practice, we routinely observed a notably high [ 18F]PSMA‑1007 uptake in the urinary bladder. The underlying reasons for this phenomenon remain inadequately explored.Purpose of the study. The purpose of this study was to assess the impact of preliminary hydration of patients on [18F]PSMA‑1007 uptake in the urinary bladder.Materials and methods. Prospective, multicenter, randomized controlled study included 180 patients with PCa who underwent [18F]PSMA‑1007 PET/CT. Scans were performed using three different PET/CT-systems: GE Discovery IQ Gen 2 (USA), Siemens Biograph 64 mCT and Biograph 64 TruePoint (Germany). All patients were divided into two groups: the group with hydration (n = 95, 53 %), which included the subgroups of patients with oral (n = 76, 80 %) and intravenous (n = 19, 20 %) routes of hydration, and the control group with no hydration (n = 85, 47 %). [18F]PSMA‑1007 uptake in the urinary bladder was quantified using SUVmean (Mean Standardized Uptake value), measured within a spherical VOI with a fixed volume of 2.5 cm3 delineating the bladder boundaries. Additionally, the TBRmean (Mean Target-to-Background Ratio), reflecting the ratio between urinary bladder and right gluteal muscles SUVmean.Results. SUVmean and TBRmean in urinary bladder were significantly lower (p < 0,001) in the group with hydration compared to the control group, with the following values: 1.3 [0.8; 2.0] versus 4.5 [2.7; 8.5] for SUVmean and 4.0 [2.3; 6.3] versus 13.0 [7.7; 24.0] for TBRmean. There was no significant differences in SUVmean and TBRmean between the subgroups with oral and intravenous routes of hydration (p = 0.95 for SUVmean, p = 0.49 for TBRmean). Additionally, comparatively lower interquartile range (IQR) values for both SUVmean and TBRmean in the group with hydration were noted: 1.2 versus 5.8 for SUVmean, 4.0 versus 16.3 for TBRmean.Conclusion. Preliminary hydration of patients in uptake period significantly reduces both the level and variability of [18F]PSMA‑1007 uptake in the urinary bladder.